The Handbook of children, media, and development - Calvert, Sandra L.; Wilson, Barbara J. (Chichester Wiley-Blackwell, 2011)
Media use starts in the first year of life. Initial experiences are controlled by parents and caregivers, but increasingly give way to childrena s preferences. The degree to which these experiences are a positive or negative source of developmental change is an ongoing intellectual debate with significant implications for today's society.
Historical and recurring concerns about children's use of the mass media / Ellen Wartella and Michael Robb Business models for children's media / Alice Cahn, Terry Kalagian, and Catherine Lyon -- Media use across childhood: Access, time, and content / Ronda Scantlin -- Children, race, ethnicity, and media / Bradley S. Greenberg and Dana E. Mastro -- Gender, media use, and effects / Stacey J.T. Hust and Jane D. Brown -- Media and the family / Alison Alexander -- Attention and learning from media during infancy and early childhood / Rachel Barr -- Media symbol systems and cognitive processes / Kaveri Subrahmanyam and Patricia Greenfield -- Learning from educational media / Heather L. Kirkorian and Daniel R. Anderson -- News, reality shows, and children's fears: Examining content patterns, theories and negative effects / Stacy L. Smith, Katherine M. Pieper, and Emily J. Moyer-Guse -- Media violence and aggression in youth / Barbara J. Wilson -- Prosocial effects of media exposue / Marie-Louise Mares, Edward Palmer, and Tia Sullivan -- Make-believe play, imagination, and creativity: Links to children's media exposure / Dorothy G. Singer, and Jerome L. Singer -- Parasocial and online social relationships / Cynthia Hoffner -- Fear responses to media entertainment / Patti M. Valkenburg and Moniek Buijzen -- Media use and childhood obesity / Elizabeth A. Vandewater and Hope M. Cummings -- Media, body image, and eating disorders / Kristen Harrison and Veronica Hefner -- Media and advertising effects / Brian Young -- Adolescents and media messages about tobacco, alcohol, and drugs / Dina L.G. Borzekowski and Victor C. Strasburger -- The Children's Television Act / Sandra L. Calvert -- Regulating the media: Sexually explicit content / Joah G. Iannotta -- Media-related policies of professional health organizations / Marie Evans Schmidt, David S. Bickham, Amy Branner, and Michael Rich -- The rating systems for media productions / Douglas A. Gentile -- Parent and school interventions: Mediation and media literacy / Jennifer L. Chakroff and Amy I. Nathansons.
Originally published: 2008.
Keywords: Mass media and children; Child development; Children's mass media